(untitled) (Alternautas, 2022)
Thousands of diverse ‘water protectors’ representing different ethnic, cultural, and social backgrounds throughout the American continent are standing firm against the destruction of ecological systems carried out by extractive development projects. One recent example concerning indigenous peoples has been the mobilization carried out by the Hunkpapa Lakota and Yanktonai Dakota Native American people of the Standing Rock Sioux reservation against the construction of the Dakota Access Pipeline. The pipeline project is a 3.8 billion investment to move 500,000 barrels of domestic crude oil a day through four U.S. states. If constructed, the Dakota pipeline would pass through sacred burial grounds as well as the Missouri river – the main water source for the Standing Rock Sioux population.